Formulation of a Traditional Polyherbal Product to a Standard Pharmaceutical Syrup and Development of Its Quality Control Methods - Maedeh Rezghi; Seyed Alireza Mortazavi*; Rasool Choopani; Shirin Fahimi; Mohammad Abbas Sheihkoleslami; Maryam Hamzeloo-Moghadam (Iranian Society of Pharmacognosy, 2019)
Background and objectives: People interest in traditional medicine has increased recently; however, traditional herbal medicines should be transformed into modern forms of medicine to increase patient acceptance. In this investigation, a polyherbal traditional combination "Monzej-e-balgham" has been based on according to Iranian traditional medicine (ITM) manuscripts and its quality control evaluations have been performed. Methods: The main ingredients of the formulation including Vitis venifera L., Ficus carica L., Foeniculum vulgare Mill., Glycyrrhiza glabra L., Adiantum capillus-veneris L., Rosa damascena Herrm. and Onopordum acanthium L. were crushed, mixed and extracted with distilled water by decoction method. The mixture was used to prepare formulations of the syrup. Physicochemical, microbiological properties and rheological behavior of the syrup were studied and total phenolics content of the formulation was determined. The syrup was evaluated in accelerated stability test during 6 months. Results: The product was light brown semitransparent syrup with appropriate taste and odor. There was no cap locking and precipitation. Dry residue, sedimentation, pH, viscosity, density and total phenolics were found to be 14.82%, 0.015%, 5.40, 4.6 cP, 1.076 g/mL and 127.34 mg/100 mL, respectively. Microbial evaluations of syrupwere consistent with the WHO protocol. The rheogram of the product represented the Newtonian behavior. In the accelerated stability tests, no significant changes were observed. Total phenolics content reduced to 2.50% within 6 months in 40 ºC. Conclusion: The outcome of this research was a pharmaceutical standardized formulation from the traditional "Monzej-e-balgham" which supports the idea of drug discovery based on traditional knowledge.